Peran Pola Asuh Orang Tua dalam Perkembangan Moral Anak Usia 5-6 Tahun di PAUD Pelangi Nusantara Indramayu - Nur Asiyah; Sumanta Sumanta; Siti Fatimah (Scidac Plus, 2023)
This research aims to describe: (1) The role of parents' democratic parenting style in the moral development of children aged 5-6 years at PAUD Pelangi Nusantara; (2) The positive effect of parents' democratic parenting style on the moral development of children aged 5-6 years at PAUD Pelangi Nusantara. This research method is a qualitative approach using data collection techniques such as observation and interviews. The data analysis process includes the stages of data collection, data reduction, data presentation, and conclusions. The findings from this research show that: (1) Democratic parenting styles of parents have an important role in the moral development of children aged 5-6 years at PAUD Pelangi Nusantara; (2) There are many benefits that come from democratic parenting on the moral development of children aged 5-6 years at PAUD Pelangi Nusantara. Some parents still apply a hereditary parenting style that tends to be authoritarian and forces children to obey, especially for children who attend PAUD Pelangi Nusantara.